2009
DOI: 10.1143/jjap.48.120205
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Morphotropic Phase Boundary in La-Doped BiFeO3–PbTiO3Piezoceramics

Abstract: BiFeO 3 -PbTiO 3 (BF-PT) powders with mixed tetragonal and rhombohedral crystal structure (morphotropic phase boundary: MPB) were modified with lanthanum to provide a wide variation in tetragonal distortion. X-ray diffraction from both the powder and the corresponding bulk ceramic demonstrated that the MPB in the bulk is shifted from 1-5 mol % towards the tetragonal PT as compared to the powder. This shift was correlated with the degree of tetragonal distortion as quantified by c=a ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 20 publications
(24 reference statements)
6
34
1
Order By: Relevance
“…An increase in the La content leads to a reduction of the c/a ratio of the tetragonal phase from 1.10 to 1.01, in agreement with previous reports. 26,27 As expected, an increase in temperature leads to a decrease in the tetragonal distortion. Measurement fits are provided to visualize the changes in the c/a ratios for each temperature.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…An increase in the La content leads to a reduction of the c/a ratio of the tetragonal phase from 1.10 to 1.01, in agreement with previous reports. 26,27 As expected, an increase in temperature leads to a decrease in the tetragonal distortion. Measurement fits are provided to visualize the changes in the c/a ratios for each temperature.…”
Section: Resultssupporting
confidence: 73%
“…However, it has been shown that even significant deviations from this ratio have little influence on material properties. 27 Details of the powder preparation and sintering procedures can be found in detail elsewhere. 27,29,34 As an effect of the lanthanum doping it was possible to tune the tetragonality from 1.10 to 1.01, 27 which was accompanied by a reduced Curie temperature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations